Design for A Remote Smart Home Monitor Using the Internet of Things (IoT) - Mita Azania Utami; Suroso Suroso; Irma Salamah (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
Designing a Remote Smart Home Monitor Based on the Internet of Things (IoT) using the NodeMCU ESP32 microcontroller as a wifi network provider and also utilizing Firebase Technology as a data storage medium. This remote smart home monitor with the Internet of Things concept is safe because only people who have certain access can control home appliances such as turning on lights, fans, opening doors, filling water in the bath, preventing theft, in Remote Smart Home Monitors also uses CCTV cameras that utilize special applications, with the selection of these communication technologies efficiently and also saving power in controlling and monitoring from smart home remotely via smartphones. Test results control data can function properly when the switch control is activated then the lights, fans, doors will automatically turn on. Test results PIR sensor can detect movement or when the door is open and the buzzer will sound sending information on the android application. Test results, the ultrasonic sensor can work when the sensor reads the water distance >15 cm then the pump will work to fill the water and when the sensor distance reads the distance <2 cm then the pump will stop to fill the water.